Human Computer Interaction for Vision Based Hand Gesture Recognition: A Survey - Hasan, Haitham Sabah; Kareem, S. Abdul (2012 International Conference on Advanced Computer Science Applications and Technologies (ACSAT), 2012)
The ultimate aim is to bring Human Computer Interaction to a regime where interactions with computers will be as natural as an interaction between humans, and to this end, incorporating gestures in HCI is an important research area. Gestures have long been considered as an interaction technique that can potentially deliver more natural, creative and intuitive methods for communicating with our computers. This paper provides a summary of previous surveys done in this area and focuses on the different application domain which employs hand gestures for efficient interaction. The use of hand gestures as a natural interface serves as a motivating force for research in gesture taxonomies, its representations and recognition techniques. Also provides an analysis of existing literature related to gesture recognition systems for human computer interaction by categorizing it based on different parameters. The main goal of this survey is to provide researchers in the field with a summary of progress achieved to date and to help identify areas where further research is needed.